A worldwide perspective on the management and control of Dothistroma needle blight. Issue 5 (22nd September 2016) - Bulman, L. S.; Bradshaw, R. E.; Fraser, S.; Martín‐García, J.; Barnes, I.; Musolin, D. L.; La Porta, N.; Woods, A. J.; Diez, J. J.; Koltay, A.; Drenkhan, R.; Ahumada, R.; et al.
Summary: Dothistroma needle blight (DNB) caused by Dothistroma septosporum and Dothistroma pini is a damaging disease of pine in many countries. The disease led to the abandonment of planting susceptible Pinus species in parts of Africa, Asia, Australasia, Europe and North America. Although the disease can be effectively controlled using copper fungicides, this chemical is only routinely applied in forests in New Zealand and Australia. Other management tactics aimed at making conditions less favourable for disease development, such as thinning or pruning, may be effective on some, but not all, sites. Disease avoidance, by planting non‐susceptible species, is the most common form of management in Europe, along with deployment of hosts with strong disease resistance. Although D. septosporum is present almost everywhere Pinus is grown, it is important that an effort is maintained to exclude introductions of new haplotypes that could increase virulence or enable host resistance to be overcome. A global strategy to exclude new introductions of Dothistroma and other damaging forest pathogens, facilitated by collaborative programmes and legislation, is needed.